REMISI DAN PENEGAKAN HUKUM PIDANA - Rois, Harliyanto (Fakultas Hukum Universitas Muhammadiyah Cirebon, 2024)
Remission is a reduction in sentence given by the state to prisoners who have met certain requirements, it can be said as a right but there is also an obligation. Criminal law enforcement is based on the principle of legality, where an act can only be punished after there are rules that regulate it before the act is committed. Murder is the taking or taking of a person's life by another person which results in the failure of all vital functions of the body due to the separation of the spirit from the victim's body. The purpose of this study is to determine remission and criminal law enforcement in cases of premeditated murder. Normative legal research method. While the approach method used is the Statute Approach. Researchers see law as a closed system that has comprehensive characteristics, namely the legal norms in it are related to one another. Data obtained from the results of the study will be analyzed using a qualitative normative analysis method. The results of this study indicate that Jessica Kumala Wongso, a convict in the premeditated murder case of Wayan Mirna Salihin, received a remission of 58 months and 30 days. This remission was given because Jessica was considered to have behaved well while serving her sentence at Pondok Bambu Prison. Jessica was released on parole based on the Decree of the Minister of Law and Human Rights of the Republic of Indonesia Number: PAS-1703.PK.05.09 of 2024. In the case of Jessica Wongso, the criminal law enforcement carried out was as follows: Jessica Wongso was charged and proven to have committed premeditated murder of Wayan Mirna Salihin by mixing cyanide poison into Vietnamese iced coffee. Jessica Wongso was sentenced to 20 years in prison based on Article 340 of the Criminal Code concerning Premeditated Murder. Jessica Wongso was released on parole on August 18, 2024 after serving 8.5 years of her sentence. Jessica received a remission of 58 months and 30 days. Keywords: Remission, Law Enforcement, Criminal